2007
DOI: 10.1111/j.1365-3059.2006.01498.x
|View full text |Cite
|
Sign up to set email alerts
|

Economic impact of Turnip mosaic virus, Cauliflower mosaic virus and Beet mosaic virus in three Kenyan vegetables

Abstract: Screenhouse experiments conducted in Kenya showed that inoculation of cabbage seedlings with Turnip mosaic virus (TuMV), either alone, or in combination with Cauliflower mosaic virus (CaMV), reduced the number and weight of marketable harvested heads. When viruses were inoculated simultaneously, 25% of cabbage heads were non-marketable, representing 20-fold loss compared with control. By contrast, inoculation with CaMV alone had insignificant effects on cabbage yield. This suggests that TuMV is the more detrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 16 publications
0
28
0
3
Order By: Relevance
“…Isolate of central Asia BtMV-K had a different host range from European and American isolates [7]. Recently, greenhouse experiments conducted in Kenya showed that early inoculation of Swiss chard with BtMV significantly impaired leaf quality (50% reduction in marketable leaf production), and the impact of disease was greatest in plants that had been inoculated at maturity [8].…”
mentioning
confidence: 99%
“…Isolate of central Asia BtMV-K had a different host range from European and American isolates [7]. Recently, greenhouse experiments conducted in Kenya showed that early inoculation of Swiss chard with BtMV significantly impaired leaf quality (50% reduction in marketable leaf production), and the impact of disease was greatest in plants that had been inoculated at maturity [8].…”
mentioning
confidence: 99%
“…One such virus is TuMV, a common aphid vectored virus that can cause symptoms of leaf mosaic, necrosis, chlorotic mottle and severe distortion, as well as reductions in plant biomass (Spence et al . ). Importantly, TuMV has been known to reduce the fitness of wild brassicas by reducing biomass, fecundity and survival (Maskell et al .…”
Section: Introductionmentioning
confidence: 97%
“…Cauliflower mosaic caulimovirus (CaMV) has a double-stranded DNA genome and is frequently found in mixed infections with the ssRNA turnip mosaic potyvirus (TuMV), particularly in plants of the genus Brassica (Spak & Novikov, 1994;Raybould et al, 1999), which may or may not lead to symptom synergism (Hunter et al, 2002;Spence et al, 2007). Strikingly, in Brassica perviridis, CaMV suppresses TuMV accumulation (Kamei et al, 1969), probably reflecting host and/or virus strain influence in the dynamic of the mixed infection.…”
Section: Introductionmentioning
confidence: 99%